2005
DOI: 10.4049/jimmunol.175.8.5024
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Anti-Inflammatory Actions of TNF-α: Inhibition of IL-12 and IL-23 via TNF Receptor 1 in Macrophages and Dendritic Cells

Abstract: IL-12 and TNF-α are central proinflammatory cytokines produced by macrophages and dendritic cells. Disregulation of TNF-α is associated with sepsis and autoimmune diseases such as rheumatoid arthritis. However, new evidence suggests an anti-inflammatory role for TNF-α. TNF-α-treated murine macrophages produced less IL-12p70 and IL-23, after stimulation with IFN-γ and LPS. Frequency of IL-12p40-producing macrophages correspondingly decreased as measured by intracellular cytokine staining. IL-12p40 production wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
73
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 59 publications
19
73
2
Order By: Relevance
“…These data substantiate a role for the TNFR p55 pathway in silencing p40 production in vivo and provide a rational explanation for the hyper-Th1 and hyper-Th17 responses observed in TNFRp55 2/2 arthritic mice. These findings are consistent with recent studies implying a functional cross-talk between TNF and IL-12p40 in in vitro studies (54), collagen-induced arthritis (42), experimental autoimmune encephalomyelitis (55), and streptococcal cell wall-induced arthritis (32). In this regard, we observed a self-limiting Yersinia-induced ReA in p40 2/2 mice (14).…”
Section: Discussionsupporting
confidence: 82%
“…These data substantiate a role for the TNFR p55 pathway in silencing p40 production in vivo and provide a rational explanation for the hyper-Th1 and hyper-Th17 responses observed in TNFRp55 2/2 arthritic mice. These findings are consistent with recent studies implying a functional cross-talk between TNF and IL-12p40 in in vitro studies (54), collagen-induced arthritis (42), experimental autoimmune encephalomyelitis (55), and streptococcal cell wall-induced arthritis (32). In this regard, we observed a self-limiting Yersinia-induced ReA in p40 2/2 mice (14).…”
Section: Discussionsupporting
confidence: 82%
“…In addition to its profound proinflammatory effects, TNF was shown to limit IL-12p40 and IL-6 production in splenic APCs, suggesting a potential immunosuppressive function (22)(23)(24). We confirmed these findings and further showed that TNF expressed by both T cells and myeloid cells, rather than TNF from a single cellular source, limited in vivo production of IL-12p40 and IL-6, which regulated the development of Th1 and Th17 cells.…”
Section: Discussionsupporting
confidence: 76%
“…Increased Th cell development in vivo could be due to several factors: TNF could directly act on T cells during Th polarization or it could affect numbers, activation status, or cytokine production of APCs (22)(23)(24). First, we tested whether TNF directly affects Th cell polarization.…”
Section: Tnf Expressed By T Cells and Myeloid Cells Regulates Il-12p40mentioning
confidence: 99%
“…In this context, greater levels of TNF-␣ are produced following the use of a high effective dose of Ag relative to lower doses, in a pattern that resembles that of IFN-␥ production. TNF-␣ has been shown in multiple models to have anti-inflammatory effects via mechanisms that include apoptosis induction, IL-12/IL-23 inhibition, or CD3 down-regulation (65)(66)(67)(68)(69). However, we clearly show that reduction of elevated IFN-␥ levels is sufficient to reverse the protective effects of treatment with a high dose of Ag, placing IFN-␥ as a central regulator of the disease process.…”
Section: Discussionmentioning
confidence: 48%